Cesarean rates and severe maternal and neonatal outcomes according to the Robson 10‐Group Classification System in Khon Kaen Province, Thailand. Issue 2 (24th November 2017) - Kankoon, Natthapong; Lumbiganon, Pisake; Kietpeerakool, Chumnan; Sangkomkamhang, Ussanee; Betrán, Ana P.; Robson, Michael
Abstract: Objective: To assess cesarean rates and maternal and neonatal outcomes in each group in the Robson 10‐Group Classification System (TGCS). Methods: In a cross‐sectional study, data were reviewed from all pregnant women who delivered at 24 government hospitals in Khon Kaen Province, Thailand, in 2014. Delivery and perinatal outcomes were recorded. Results: Of 18 043 deliveries, 5666 (31.4%) were by cesarean. Women in group 5 (previous cesarean) accounted for the most cesareans (1472, 26.0%). Groups 1 and 2 (nulliparous women) accounted for 2355 (41.6%) of procedures; the rate of cesarean within these two groups was 19.4% (1162/5981) and 71.2% (1193/1675), respectively. As compared with group 1, women in groups 2, 4, 6, 7, and 10 had significantly increased risk of severe maternal outcomes, and those in groups 6, 7, 8, 9, and 10 had an increased risk of severe neonatal outcomes. Conclusion: The rate of cesarean in the study setting was high, and three out of four procedures were performed for women in groups 5, 1, and 2. Interventions should be focused on these groups to reduce the overall cesarean rates. Abstract : The overall rate of cesarean was high; three of four procedures were performed for women in Robson groups 5, 1, and 2.